Assessing The Relationship Between Dental Practitioners’ Empathy And Emotional Intelligence In A Public Institute. A Cross-Sectional Study - Siddiqui, Asma; Aftab, Rabia; Ahmed, Narmeen; Ayub, Ramsha; Sarfaraz, Shaur; Sabhi, Qudsia (Journal of Rawalpindi Medical College, 2025)
Objective: The purpose of the study is to determine the relationship between empathy and emotional intelligence among dental at a public institute in Karachi. Method: A cross-sectional study was conducted at Karachi Medical & Dental College from January 2023 to August . For this study, we targeted 250 active dental practitioners that including fresh dental graduates, dental consultants and postgraduate residents. Data collection tools used in this study were the HP (Health Professionals) version of the JSPE scale and Schutte’s Emotional Intelligence Scale (SEIS). SPSS 2 with Mann-Whitney U Test, Kruskal-Wallis Test, one ANOVA and Pearson correlation was applied to test the hypothesis. Results: Out of 250 targeted participants, 224 responses were received (response rate 89.6%). Mann-Whitney U Test and the Kruskal-Wallis test showed a statistically significant relation between empathy with gender and dental practitioners stratified according to qualification, with a p value of 0.044 and 0.012, respectively. Pearson correlation test showed a moderate correlation between empathy and emotional intelligence of dental practitioners an R-value of 0.0682. Conclusion: This study found significant variation in empathy by gender, qualification, and occupation of the participant, while EI only differed between occupations. The finding in this study supports the inclusion of emotional competency training in dental education, primarily focused on providing better patient-centred and dental care for our patients. Keywords: Empathy, emotional intelligence, dentistry, dentists, education .